Attributing forest responses to global‐change drivers: limited evidence of a CO2‐fertilization effect in Iberian pine growth. (1st September 2015) - Camarero, J. Julio; Gazol, Antonio; Tardif, Jacques C.; Conciatori, France
Abstract Aim Forest responses to global‐change drivers such as rising atmospheric CO2 concentrations (Ca), warming temperatures and increased aridification will depend on tree species and site characteristics. We aim to determine if rising Ca enhances growth of coexisting pine species along broad ecological gradients in a drought‐prone area. Location Iberian Range, Spain. Methods We sampled 557 trees of five pine species encompassing a wide climatic gradient and measured their radial growth. We used nonlinear flexible statistics (generalized additive mixed models) to characterize growth trends and relate them to Ca, temperature and water balance. Results The sites most responsive to the growing‐season water balance were dominated by Pinus pinaster and Pinus nigra at low elevations, whereas those most responsive to temperatures were high‐elevation Pinus sylvestris and Pinus uncinata stands. From 1950 onwards, most sites and species showed decreasing radial growth trends. Growth trends were coherent with a CO2‐related fertilization effect only in one P. sylvestris site. Main conclusions We found little evidence of growth stimulation of Iberian pine forests due to rising Ca. The results indicated that any positive effect of a Ca‐induced growth increase was unlikely to reverse or cancel out the drought‐driven trends of reduced growth in most Mediterranean pine forests. Further assessments of CO2‐fertilization effects on forest growth should be carried out in sites where climatic stressors such as drought do not override the effects of rising Ca on forest growth.